VD_FINDINFO Jug / 2017 / 7 vom 25. August 2016 - VD Tribunal cantonal (2016)
TENTATIVEDROIT PÉNAL, MEURTRE, COMMERCE DE STUPÉFIANTS, DOL ÉVENTUEL, CONSTATATION DES FAITS, RÉVOCATION DU SURSIS | 12 al. 2 CP, 22 ad 111 CP, 46 CP, 19 ch. 2 LStup, 10 CPP (CH)